Security, Order and Community Obedience as Preconditions for Tourism Destination Competitiveness - Chairuddin, M. Awal; Syam, Husain; Akib, Haedar (PINISI Discretion Review, 2023)
be considered by the local government and stakeholders in each region. Security and order are "public goods" that are needed by every citizen. This article explains the actual condition of tourism destination management in the aspects of security and order and community obedience. The type of qualitative research with a phenomenological approach is used to explain the noumena (meaning) behind the phenomenon (fact) regarding security, order and obedience of the people of Tana Toraja Indonesia. The results of the study found that the actual situation and conditions were created that were safe and orderly as a form of obedience of citizens to tourism destinations in Tana Toraja. The situation and conditions are created not only because it is a manifestation of the local cultural values of the Toraja people who are happy to receive visitors or tourists, but also a proof of the success of the institution of the Republic of Indonesia Police (Polri) through the role of Bhayangkara Pembina Keamanan dan Ketertiban (Bhabinkamtibmas) together with the institution of the Indonesian National Army (TNI) through the role of its personnel at the lower level. The synergy of these roles supported by obedience and active participation of the local community can be of added value as a precondition for competitive advantage in the development of sustainable tourism destinations based on community participation.